Concentrations of Metals in Fishes from the Athabasca and Slave Rivers of Northern Canada. (22nd September 2020) - Tendler, Brett; Ohiozebau, Ehimai; Codling, Garry; Giesy, John P.; Jones, Paul D.
Abstract: There is growing concern about possible effects of exploitation of the Alberta Oil Sands on the ambient environment, including possible effects on populations of fishes in the Athabasca River and farther downstream in Lake Athabasca and the Slave River. In the present study, concentrations of metals in dorsal muscle tissue of 5 fish species—goldeye, northern pike, walleye, whitefish, and burbot—from the Slave, Peace, and Athabasca Rivers were quantified. A suite of 25 metals including As, Hg, Se, Tl, and V was analyzed. Most metals exhibited no significant variations in concentration among locations. Concentrations of 5 metals, As, Hg, Se, Tl, and V, revealed significant variations among locations and were of sufficient magnitude to be of interest. Concentrations of Hg did not vary significantly among locations; however, because it was detected at concentrations of concern and the use of the selected fishes was a local source of food for humans and pets, it was of interest. Concentrations of As, Se, Tl, and V in dorsal muscle of certain fishes in the farthest downstream sites on the Slave River were greater than those in the same tissues and species in the farther upstream sites on the Peace and Athabasca Rivers. This phenomenon was most prevalent with Tl and to a lesser extent with As and Se. Nevertheless, concentrations were not of concern for the health of human consumers. Although metals did not appear to be increased in fish in the Alberta Oil Sands region in the present study, further research is needed to understand the potential impacts. Environ Toxicol Chem 2020;39:2180–2195. © 2020 SETAC